(untitled) (Palestine Issues on Indonesian Society, 2024)
This paper analyzes how the Palestinian issue is represented in Indonesian educational curricula and the political implications of its inclusion. The study investigates how Palestinian history, the Israeli occupation, and the broader Middle Eastern conflict are taught in schools and universities, particularly in the context of Indonesia’s educational framework. It explores how these teachings shape the national consciousness, influence student perspectives on global justice, and align with Indonesia’s foreign policy stance. The paper also examines the pedagogical strategies employed by educators and the challenges they face in navigating politically sensitive subjects. Furthermore, it highlights the role of educational institutions in fostering international solidarity with Palestine, especially among youth, and assesses the impact of these educational discourses on the formation of Indonesian identity and political attitudes. The study concludes by discussing the implications of this curriculum for Indonesia’s future foreign relations and international engagement.